Reasons For Divorce in The Compilation of Islamic Law: An Overview of Islamic Legal Psychology - Muhammad Irfanudin Kurniawan; Adi Nur Rohman (KRTHA BHAYANGKARA, 2023)
This article aims to reveal the reasons for juridical divorce and further reveal the psychological factors contained in the reasons for divorce in the Islamic Law Compilation. Through a psychological approach (psychological approach) and legislation (statute approach), the authors analyze descriptively and analytically based on materials collected through literature study. The result is that the reasons for divorce as stated in the KHI show the existence of psychological relationships such as mental readiness, the level of maturity and maturity of thought and accuracy in making decisions when having to divorce a partner. That in the reasons for divorce there are psychological factors that directly influence the occurrence of divorce.